A critical review of recent trends in second language syllabus design and curriculum development - javad zare (Al-Qanṭara, 2022)
Abstract To date, numerous books and research articles have focused on the notion of syllabus design and curriculum development. Nevertheless, very few works have had an inclusive and concise look upon the issue. This paper is an account of current trends on syllabus design and curriculum development in Second Language Acquisition in the recent past decades. This is hopefully intended to offer a descriptive and critical interpretation of the existing syllabuses in the domain of language learning and teaching. After a brief introductory remark on curriculum and syllabus types, 13 of the most prominent syllabuses in SLA will be elaborated on separately. In pursuit of doing so, definition, rationale, merits, and drawbacks attributed to each syllabus will be touched upon. Although the emergence of some of these syllabi coincides with each other, while presenting them, it has been tried to follow a roughly chronological order of their emergence.